A comparative study of various polyelectrolyte/nanocomposite electrode combinations in symmetric supercapacitors. (21st June 2019) - Cevik, Emre; Gunday, Seyda Tugba; Akhtar, Sultan; Bozkurt, Ayhan
Abstract: A more practical, nontoxic and cheaper electrolyte, poly(2-acrylamido-2-methyl-1-propanesulfonic acid) (PAMPS) was used to construct supercapacitors with different nanocomposite electrodes. The flexible devices were fabricated including active carbon (AC) electrode and nanocomposites electrodes of AC/nano-silica (nano-SiO2 ) and AC/multiwalled carbon nanotubes (MWCNTs) at various weight percentages. The symmetrical cell made from AC electrodes generated a maximum specific capacitance (Cs) of 315 F g −1 at 0.5 A g −1 . The energy density of this device was 55.5 Wh kg −1  at a power density of 690 W kg −1 . Excellent performance was achieved after 5000 charge-discharge cycles where the supercapacitor maintains 92% of its activity. The energy storage capability of the supercapacitors was also investigated with the addition of nano-SiO2 and MWCNTs. The Cs of the supercapacitors made with the electrodes AC/nano-SiO2 (5%, 10%, 25% and 50%) were 172, 228, 247 and 55 F g −1, respectively. Similarly, the capacity of the device including the electrodes of AC/MWCNTs (5%, 10%, 25% and 50%) varied as 191, 244, 93 and 20 F g −1 at 0.5 A g −1 . The maximum energy density of the devices having nano-SiO2 and MWCNT were 44.4 Wh kg −1 and 43.8 Wh kg −1, respectively at a power density of 520 W kg −1 . A supercapacitor with certain dimension successfully operated a light-emitting diode (LED). Highlights: Nanocomposite electrodes were produced for supercapacitor application. Al/Electrode/PAMPS/Electrode/Al based devices were fabricated. Maximum specific capacitance of 315 F g −1 at 0.5 A g −1 was produced. The capacitance retention of the device was 92% after 5000.